Neurendocrine tumor of common hepatic duct: an uncommon site tumor - Srivastava, Pallavi; Shukla, Saumya; Husain, Nuzhat; Sameer, Priyanka (Journal of Pathology of Nepal, 2019)
The neuroendocrine tumor of extrahepatic biliary tract is a rare neoplasm of the gastrointestinal tract. We present a case of 16 year old male presenting with epigastric pain and jaundice with a well-defined lesion in common hepatic duct on imaging. The patient underwent tumor resection. Histopathology examination revealed thickened common hepatic duct infiltrated by tumor cells with expression of Pan CK, Synaptophysin & Chromogranin with Ki- 67 proliferation index of 5%. The final diagnosis of Neuroendocrine tumor of Common Hepatic Duct, grade 2 was rendered. The patient showed no recurrence to date without intravenous chemotherapy.